DEVELOPMENT OF THE THEORY AND PRACTICE OF PHYSICAL EDUCATION OF DOMESTIC PRESCHOOL EDUCATION IN THE PERIOD OF THE RUSSIAN EMPIRE - Nataliya Panhelova; Nataliya Moskalenko (Фізичне виховання, спорт і культура здоров’я у сучасному суспільстві, 2017)
The article highlights the characteristic features of the concepts of physical education of preschool children of domestic pedagogy during the Russian Empire (18th-early–20th centuries). It is shown that the domestic pre-school practice promotes the idea of universal education, and innovative pedagogical ideas are used for the all-round education of the younger generation. Objectively, those pedagogical ideas and theories, which expressed the growing social demand for the improvement of forms and methods of upbringing contributed to the further development of pedagogical theory and practice in the field of physical education. The views and pedagogical ideas of P. F. Lesgaft, K. D. Ushynsky, I. A. Sikorsky, V. M. Bekhterev, S. F. Rusova, and others have been examined. It has been determined that the basic idea of domestic preschool pedagogy is the all-round development of a personality.